2014
DOI: 10.1128/iai.01542-14
|View full text |Cite
|
Sign up to set email alerts
|

IsdC from Staphylococcus lugdunensis Induces Biofilm Formation under Low-Iron Growth Conditions

Abstract: Staphylococcus lugdunensis is a coagulase-negative staphylococcus that is a commensal of humans and an opportunistic pathogen. It can cause a spectrum of infections, including those that are associated with the ability to form biofilm, such as occurs with endocarditis or indwelling medical devices. The genome sequences of two strains revealed the presence of orthologues of the ica genes that are responsible for synthesis of poly-N-acetylglucosamine (PNAG) that is commonly associated with biofilm in other staph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 47 publications
0
39
1
Order By: Relevance
“…Previous bioinformatics analysis has identified an N-terminal export signal (aa [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] for Sbp (30), to study its structure and interaction in vitro, a recombinant Sbp (rSbp, aa 21-169) without its export signal was expressed in BL21(DE3) and purified by affinity, ion exchange and size exclusion chromatography. The 6×His tag was removed by TEV protease cleavage, purified rSbp elutes as a single peak in size-exclusion chromatography (SEC) and was shown as a single band in SDS-PAGE, indicting high homogeneity of the rSbp protein in solution ( Figure S1).…”
Section: Sbp Is Monomeric and Partially Folded In Solution-mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous bioinformatics analysis has identified an N-terminal export signal (aa [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] for Sbp (30), to study its structure and interaction in vitro, a recombinant Sbp (rSbp, aa 21-169) without its export signal was expressed in BL21(DE3) and purified by affinity, ion exchange and size exclusion chromatography. The 6×His tag was removed by TEV protease cleavage, purified rSbp elutes as a single peak in size-exclusion chromatography (SEC) and was shown as a single band in SDS-PAGE, indicting high homogeneity of the rSbp protein in solution ( Figure S1).…”
Section: Sbp Is Monomeric and Partially Folded In Solution-mentioning
confidence: 99%
“…Recent structural studies revealed that the G5-E repeats can undergo a Zn 2+ -dependent homophilic interaction, suggesting that two identical Aap molecules expressed on the surface of neighboring cells may interact with each other and promote cell-cell accumulation during biofilm development (11,12). Besides Aap, specific homophilic interactions have been identified for SraP (13), IsdC (14), SasG (15) and SdrC (16) mediated biofilm accumulation, thus, homophilic . interactions appear to be a common mechanism by which the matrix proteins promote biofilm formation.…”
mentioning
confidence: 99%
“…Although the polycationic polysaccharide intercellular adhesin has long been thought to be the main component promoting intercellular adhesion (4,5), there is now a compelling body of evidence that cell wall-anchored (CWA) proteins are also involved (2,3). Several recombinant CWA proteins have been shown to form dimers in solution (6)(7)(8)(9). In some cases (i.e., Aap), crystallographic studies have provided insights into the mechanism of dimer formation (9,10).…”
mentioning
confidence: 99%
“…A role for the surface protein IsdC in cell-cell attachment and biofilm formation under iron deplete conditions was shown for Staphylococcus lugdunensis (Missineo et al 2014). Interestingly, this protein is a homolog of BC4549, encoding a component of the IlsA iron transporting system.…”
Section: Iron Sources and Biofilm Formationmentioning
confidence: 99%
“…In P. aeruginosa cell aggregation, either via growth in a colony or by means of exopolysaccharide (EPS) production, has been shown to trigger the production of the siderophore pyoverdine and other virulence factors (Visaggio et al 2015). In Staphylococcus lugdunensis, the cell wall bound IsdC protein involved in iron transport promoted cell aggregation in iron depleted condition (Missineo et al 2014). Such mechanisms of linking iron transport with biofilm formation may also be present in B. cereus and require further study.…”
Section: Iron Sources and Biofilmmentioning
confidence: 99%